INTEGRATION OF NANOTECHNOLOGY AND REGENERATIVE MEDICINE FOR NEXT-GENERATION HEALTHCARE SOLUTIONS - Kiran Iqbal; Ahmed Shah; Sara Hussain (Journal of Biomedical and Techno Nanomaterials, 2026)
Nanotechnology and regenerative medicine are two rapidly evolving fields with the potential to transform healthcare by providing advanced solutions for tissue repair, disease treatment, and personalized medicine. The integration of nanotechnology with regenerative medicine offers the opportunity to enhance the efficacy of stem cell therapies, drug delivery systems, and tissue engineering, enabling more precise and effective treatments. Despite promising results, challenges remain regarding the scalability, biocompatibility, and long-term safety of nanomaterials in clinical applications. This study aims to explore the integration of nanotechnology with regenerative medicine to develop next-generation healthcare solutions. It focuses on evaluating the potential applications, challenges, and future directions of nanomaterial-based therapies in tissue regeneration and disease management. A systematic review of the current literature on nanotechnology and regenerative medicine was conducted. The review included studies on nanomaterials used for tissue engineering, drug delivery, and stem cell therapies. In vitro and in vivo research data were analyzed to assess the effectiveness and biocompatibility of nanomaterial-based approaches. The findings indicate that nanomaterial-based systems significantly improve the performance of regenerative medicine therapies, offering enhanced tissue regeneration, targeted drug delivery, and better integration with biological systems. However, issues like material stability and immune response remain. The integration of nanotechnology and regenerative medicine holds significant potential for advancing healthcare solutions. Addressing the current challenges will be critical for the successful translation of these technologies into clinical practice.